Stereoselective Biocatalyzed Reductions of Ginger Active Components Recovered from Industrial Wastes. (3rd March 2022) - Nasti, Rita; Bassanini, Ivan; Ferrandi, Erica Elisa; Linguardo, Federica; Bertuletti, Susanna; Vanoni, Marta; Riva, Sergio; Verotta, Luisella; Monti, Daniela
Abstract: Ginger is among the most widespread and widely consumed traditional medicinal plants around the world. Its beneficial effects, which comprise e. g. anticancer and anti‐inflammatory activities as well as gastrointestinal regulatory effects, are generally attributed to a family of non‐volatile compounds characterized by an arylalkyl long‐chained alcohol, diol, or ketone moiety. In this work, ginger active components have been successfully recovered from industrial waste biomass of fermented ginger. Moreover, their recovery has been combined with the first systematic study of the stereoselective reduction of gingerol‐like compounds by isolated alcohol dehydrogenases (ADHs), obtaining the enantioenriched sec ‐alcohol derivatives via a sustainable biocatalytic path in up to >99 % conversions and >99 % enantiomeric/diastereomeric excesses. Abstract : Ginger active constituents have been successfully recovered from industrial waste biomasses of fermented ginger and converted into the corresponding diols and alcohols by stereoselective biocatalyzed reductions.